2018
DOI: 10.21776/ub.habitat.2018.029.3.13
|View full text |Cite
|
Sign up to set email alerts
|

Analisis Dampak Pengembangan Wisata Pulau Bokori Terhadap Kondisi Sosial Ekonomi Masyarakat Bajo (Studi Kasus di Desa Mekar Kecamatan Soropia)

Abstract: Pulau Bokori merupakan salah satu destinasi wisata bahari yang menjadi tempat tujuan pariwisata di Sulawesi Tenggara. Pengembangan Pulau Bokori yang dilakukan pemerintah daerah secara langsung akan memberikan pengaruh bagi masyarakat sekitar. Masyarakat Bajo di Desa Mekar adalah masyarakat yang mendiami daerah sekitar pulau bokori dengan mata pencaharian sebagai nelayan dengan tingkat kemiskinan yang sangat tinggi yakni seluruh masyarakatnya tergolong masyarakat miskin. Keberadaan wisata pulau bokori ini akan … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
2
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 1 publication
0
2
0
4
Order By: Relevance
“…awareness to maintain the environmental cleanliness, improving community welfare, providing opportunities for the local community to be involved in resource and tourism management. Another 4% respondent indicated that there will be a negative impact, such as beach damaged and large amounts of plastic waste caused by tourists (Figure 6) The same thing is mentioned in the research of Dritasto & Anggraeni (2013) and Fyka et al, (2018) regarding the impact of tourism on the economy where the community's economy increases due to the existence of community business units such as crossing service, mat rental, and food sellers. Fyka et al (2018) mentioned that tourism has an impact on changing the lifestyle of the local community through the way they dress and communicate.…”
Section: No 22%mentioning
confidence: 72%
See 1 more Smart Citation
“…awareness to maintain the environmental cleanliness, improving community welfare, providing opportunities for the local community to be involved in resource and tourism management. Another 4% respondent indicated that there will be a negative impact, such as beach damaged and large amounts of plastic waste caused by tourists (Figure 6) The same thing is mentioned in the research of Dritasto & Anggraeni (2013) and Fyka et al, (2018) regarding the impact of tourism on the economy where the community's economy increases due to the existence of community business units such as crossing service, mat rental, and food sellers. Fyka et al (2018) mentioned that tourism has an impact on changing the lifestyle of the local community through the way they dress and communicate.…”
Section: No 22%mentioning
confidence: 72%
“…Another 4% respondent indicated that there will be a negative impact, such as beach damaged and large amounts of plastic waste caused by tourists (Figure 6) The same thing is mentioned in the research of Dritasto & Anggraeni (2013) and Fyka et al, (2018) regarding the impact of tourism on the economy where the community's economy increases due to the existence of community business units such as crossing service, mat rental, and food sellers. Fyka et al (2018) mentioned that tourism has an impact on changing the lifestyle of the local community through the way they dress and communicate. And there is also an impact to the environment due to tourism activity such as in Khirsnamurti et al (2016) in Tidung Island which shows that the tourism activity has an impact on the visual changes of Tidung Island because of the large number of homestays and accumulation of waste caused by an imbalance in waste management with the amount of waste generated by tourists.…”
Section: No 22%mentioning
confidence: 72%
“…Sub sektor kelautan merupakan sektor yang memanfaatkan ruang laut sebagai sumber aktivitas adalah wisata bahari Fyka et al, 2018). Berbagai potensi sumber daya laut seperti pesisir dan ekosistem terumbu karang merupakan daya tarik bagi wisatawan lokal maupun mancanegara.…”
Section: Pendahuluanunclassified
“…Kunjungan wisatawan lokal maupun asing ke suatu Daerah Tujuan Wisata (DTW) dapat memberikan dampak positif bagi masyarakat sekitar, diantaranya dapat meningkatkan penghasilan masyarakat sekitar, memperluas kesempatan kerja serta meningkatkan pendapatan asli daerah dari retribusi wisata. Namun tak dapat dipungkiri, sektor pariwisata juga berpotensi dalam memicu perubahan perilaku masyarakat sekitar, memudarnya nilai dan norma sosial, serta pencemaran lingkungan (Fyka et al, 2018). Hal tersebut menjadi pertimbangan pemerintah bagaimana mengelola sektor pariwisata dengan baik sehingga dapat meminimalisir potensi negatif dengan melakukan kerjasama dan kontrol dengan dinas-dinas terkait, masyarakat lokal serta para wisatawan.…”
Section: Pendahuluanunclassified